2013
DOI: 10.1016/j.vaccine.2012.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity following the first and second doses of 7-valent pneumococcal conjugate vaccine in HIV-infected and -uninfected infants

Abstract: Background The immunogenicity of pneumococcal conjugate vaccine (PCV) has not been evaluated in HIV-infected infants following the first and second PCV-doses. We studied antibody kinetics of serotypes included in 7-valent PCV in HIV-infected and HIV-uninfected infants prior to and following each of three PCV-doses. Methods HIV-uninfected infants born to HIV-uninfected (HUU) and HIV-infected mothers (HEU); and perinatal HIV-infected children with CD4+ < 25% randomized to initiate antiretroviral treatment (ART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…Immune responses in HIV+ children with percentages of CD4+ cells ≥25% (signifying immuno-competence) have been previously assessed for PCV7; [16,18] higher antibody concentrations were observed post-primary vaccination in HIV+ children on ART than in HUU children, with similar OPA titres (except for 19F and 23F). [16] …”
Section: Discussionmentioning
confidence: 99%
“…Immune responses in HIV+ children with percentages of CD4+ cells ≥25% (signifying immuno-competence) have been previously assessed for PCV7; [16,18] higher antibody concentrations were observed post-primary vaccination in HIV+ children on ART than in HUU children, with similar OPA titres (except for 19F and 23F). [16] …”
Section: Discussionmentioning
confidence: 99%
“…Prevnar®; Wyeth Vaccines, NJ, USA), administered at 6, 10 and 14 weeks of age was evaluated. [15, 16] Briefly, PCV7 was administered concurrently with other recommended childhood vaccines in South Africa, including H. influenzae type-b conjugate vaccine (HibCV). Infants were enrolled in Soweto (Gauteng) and Tygerberg (Western Cape) in South Africa from April 2005 to June 2006.…”
Section: Methodsmentioning
confidence: 99%
“…The immune responses following two doses of PCV given at 6 and 10 weeks of age were, however, similar in HIV-infected SA infants on ART compared with HIV-uninfected SA infants. [25] Furthermore, provisional results of a case-control study also showed that PCV-immunised, HIV-uninfected children were 27% (95% CI 0 -49) less likely than unimmunised children to be hospitalised for presumed bacterial pneumonia. [26] A multi-centre, case-control study to evaluate the effectiveness of RV against rotavirus-associated diarrhoea hospitalisation is also nearing completion.…”
Section: Effectiveness Of Pcv and Rv In Samentioning
confidence: 99%